2017
DOI: 10.4103/sni.sni_222_17
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of surgical site infections in instrumented spine surgery

Abstract: Background:The incidence of wound infections associated with instrumented spine surgery ranges from 2 to 20%. These complications may lead to poor outcomes. Knowing the risk factors associated with surgical site infections (SSI) after utilizing spinal implants is essential to avoid these complications, including hardware removal.Methods:We reviewed retrospectively 550 patients who underwent spinal fusion surgery from 2011 to 2015; 16 developed SSI after spinal instrumentation. The diagnosis of SSI was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
0
28
0
3
Order By: Relevance
“…[34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection. Additionally, when utilizing a posterior approach, obese patients can create a more technically demanding procedure due to limited patient mobility and increased difficulty during surgical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection. Additionally, when utilizing a posterior approach, obese patients can create a more technically demanding procedure due to limited patient mobility and increased difficulty during surgical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These results are partly due to pathophysiological changes and high rate of complications secondary to DC. Rebleeding, encephalocele, cerebral infarction, SE, cerebrospinal fluid leakage from incision, intracranial infection, paradoxical herniation, hydrocephalus, skull defect syndrome and epilepsy are main complications [14][15][16]. In this study, the incidence of common complications ranged from 0.9% to 58.3%.…”
Section: Discussionmentioning
confidence: 70%
“…Surgical site infection after instrumented spine surgery is a challenging pathology for diagnosis and treatment. [1][2][3][4] There are many peri-operative risk factors of SSI documented in literature, such as obesity 7 and the described patient was obese with BMI>30.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In the literature, the and Propionibacterium acnes. [1][2][3][4] The etiopathogenetic mechanism has not yet been clearly defined, but there are two possibilities: contamination of microorganisms during surgery or in the postoperative period and haematogenous spread.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation